CAMELLIA HOAANA (THEACEAE, SECTION CORALLINA), A NEW SPECIES FROM BU GIA MAP NATIONAL PARK IN SOUTHERN VIETNAM - Shi-Xiong Yang; Dinh Thap Kieu; Trong Hung Le; Huu Thang Khuong (Tạp chí Khoa học Đại học Đà Lạt)
Camellia hoaana, a new species of the Camellia sect. Corallina (Theaceae) from Bu Gia Map National Park, Vietnam, is described and illustrated. Morphological features of this species are young branches pubescent and glabrescent. Leaves elliptic to obovate-elliptic; apex bluntly cuspidate, base wide cuneate; above dark green, shiny and glabrous; below paler green and sparsely pubescent along midrib; petiole sparsely pubescent. Flowers solitary or geminate, axillary or terminal; pedicel pubescent. Bracteole 1 (or none),pubescent on both sides, persistent. Sepals 4–5(–6), pubescent on both sides, persistent. Petals 5–6, white, outermost 1–2 pubescent at the apex on both sides, the rest glabrous on both sides. Androecium numerous, 2–3 whorls, glabrous. Ovary 3-locular, white silky tomentose; styles 3, free to the base, glabrous. Capsule subglobose, sparsely pubescent, furfuraceous. Seeds 1–2 per locule, semiglobose or globose, densely brown villous. This new species is assessed as Data Deficient (DD) according to the IUCN categories and criteria.